The Economic Importance of the Productive Goodly Loan in Supporting Small Productive Projects in Iraq - Attallah, Mohammed Noori; Hussein, Soori Yassin (International Journal of Psychosocial Rehabilitation, 2020)
The use of the loan as a means of financing for the purpose of growing projects and achieving development is unique to Islamic law through the contribution of the able and rich in supporting the poor and needy, by providing liquidity for small productive projects, such as industries involving people with simple crafts and professions, under which the lender waives its right of return on investment to the borrower, considering that he be rewarded by Allah almighty in the other world as he offers an investment opportunity for his brother who has the ability and experience to invest. The loan provided generates an economic value represented by the self-sufficiency that the borrowers will enjoy, in addition to achieving justice that arises because of the real distribution of resources, helping in the establishment of a human community that is interdependent. Through the application of the goodly loan we get a combination between the element of creative work (represented by the investor) and the element of capital so that to legitimately employ funds in economic activities that serve the economic development. The study aimed to demonstrate the importance of the goodly loan and its impact in pushing small economic projects and activities, and then demonstrating the role of these projects in the performance of the national economy - especially in Iraq. The study showed the economic importance of the productive goodly loan for the owner of the project "the investor", as well as the role of the loan in stirring up the process of production as well as the economy. Finally, the study presented a number of recommendations aimed at improving the reality of such pioneer projects and their role in achieving a balanced economic development.